(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The present study aimed to examine the effectiveness of a group-play–based program in developing linguistic communication skills among children with Autism Spectrum Disorder (ASD). The study was conducted on a sample of 32 children with ASD, aged between 4 and 6 years, with a mean age of 5.6 years and a standard deviation of 0.87. The participants were equally assigned to an experimental group and a control group. A quasi-experimental design was employed to implement the study procedures. The study instruments included the Linguistic Communication Scale (developed by the researcher) and the group-play–based program (designed by the researcher). The findings revealed the effectiveness of the program, as statistically significant differences were found between the pre-test and post-test mean ranks of the experimental group on the Linguistic Communication Scale in favor of the post-test. Furthermore, statistically significant differences were observed between the experimental and control groups on the post-test in favor of the experimental group. However, no statistically significant differences were found between the post-test and follow-up test scores of the experimental group. The study recommended the adoption of group play as an effective strategy to enhance linguistic communication skills among children with ASD.